Association between Tumor Vasculogenic Mimicry and the Poor Prognosis of Gastric Cancer in China: An Updated Systematic Review and Meta-Analysis. (12th October 2016) - Guo, Qiujun; Yuan, Yuan; Jin, Zhichao; Xu, Tao; Gao, Yebo; Wei, Huamin; Li, Conghuang; Hou, Wei; Hua, Baojin
Abstract : Background . Vasculogenic mimicry can promote tumor growth and metastasis. This article is aimed at conducting a systematic meta-analysis to explore the clinicopathological and prognostic significance of vasculogenic mimicry and gastric cancer. Methods . We searched Pubmed, EMBASE, Cochrane Library, China National Knowledge Infrastructure, and the VIP and Wanfang Database for eligible studies. We manually searched for printed journals and relevant textbooks. Subgroups analyses were performed based on the region, manuscript quality, methods of vasculogenic mimicry identification, pathology, and number of patients. Results . Nine studies with 997 patients were included in this meta-analysis. A significant association was observed between vasculogenic mimicry-positive patients and those with gastric cancer with poor overall survival (hazard ratio = 2.24, 95% confidence interval: 1.45–3.47), poor pathological grading, high tumor node metastasis clinical stage, lymph node metastasis, deep tumor invasion, and distant metastasis. Conclusions . Vasculogenic mimicry is associated with a poor prognosis in patients with gastric cancer in China. Clinical studies with large samples are needed worldwide and standardized protocols should be adopted in the future to achieve a better understanding of the relationship between gastric cancer and vasculogenic mimicry.